2018
DOI: 10.1111/gcbb.12517
|View full text |Cite
|
Sign up to set email alerts
|

Increased CO2 fluxes from a sandy Cambisol under agricultural use in the Wendland region, Northern Germany, three years after biochar substrates application

Abstract: In recent years, biochar has been discussed as an opportunity for carbon sequestration in arable soils. Field experiments under realistic conditions investigating the CO 2 emission from soil after biochar combined with fertilizer additions are scarce. Therefore, we investigated the CO 2 emission and its 13 C signature after addition of compost, biogas digestate (originating from C4 feedstock) and mineral fertilizer with and without biochar (0, 3, 10, 40 Mg biochar/ha) to a sandy Cambisol in Northern Germany. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…No biochar effects on CO 2 fluxes were found in previous field experiments using relatively low biochar application rates (< 10 t ha −1 ) (Karhu, Mattila, Bergström, & Regina, 2011;Mechler, Jiang, Silverthorn, & Oelbermann, 2018;Sackett et al, 2015), which is confirmed by the results from the B and D:BL treatments in the current field experiments. Also, Polifka, Wiedner, and Glaser (2018) found no significant increase of mean CO 2 fluxes from heterotrophic respiration when they applied a mixture of biogas plant digestates and biochar on a Cambisol in northern Germany at low biochar application rates (3 t ha −1 ). In contrast, when applying high biochar application rates (40 t ha −1 ), a strong (53%) and significant increase of CO 2 fluxes was found (Polifka et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…No biochar effects on CO 2 fluxes were found in previous field experiments using relatively low biochar application rates (< 10 t ha −1 ) (Karhu, Mattila, Bergström, & Regina, 2011;Mechler, Jiang, Silverthorn, & Oelbermann, 2018;Sackett et al, 2015), which is confirmed by the results from the B and D:BL treatments in the current field experiments. Also, Polifka, Wiedner, and Glaser (2018) found no significant increase of mean CO 2 fluxes from heterotrophic respiration when they applied a mixture of biogas plant digestates and biochar on a Cambisol in northern Germany at low biochar application rates (3 t ha −1 ). In contrast, when applying high biochar application rates (40 t ha −1 ), a strong (53%) and significant increase of CO 2 fluxes was found (Polifka et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Also, Polifka, Wiedner, and Glaser (2018) found no significant increase of mean CO 2 fluxes from heterotrophic respiration when they applied a mixture of biogas plant digestates and biochar on a Cambisol in northern Germany at low biochar application rates (3 t ha −1 ). In contrast, when applying high biochar application rates (40 t ha −1 ), a strong (53%) and significant increase of CO 2 fluxes was found (Polifka et al, 2018). However, the increased CO 2 fluxes only accounted for about 0.3% of the added biochar, indicating a substantial sequestration of carbon after biochar application.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Plant-available nitrogen during winter rye growing season seems to be lower for the digestate, fermented digestate and compost treatments reflected in reduced nitrogen uptake. However, it should be noted that, albeit not significant, high biochar application rates increased the average nitrogen uptake in three fertilizer groups, which could be probably explained by increased cation exchange capacity as shown by Glaser et al (2015) or due to a higher mineralization rate through an increased microbial activity favored by the high porosity of biochar (Thies and Rillig 2009;Lehmann et al 2011;Polifka et al 2018). Due to its biological nitrogen fixation (BNF) properties, lupine holds a special position within this field experiment and the results are difficult to compare with maize and winter rye grown in two previous years of this experiment.…”
Section: Biochar Effect On Nitrogen Uptake Of Winter Rye and Lupinementioning
confidence: 83%
“…Of the ten total treatments established in 2012 ( Glaser et al., ; Polifka et al., ), six treatments were analyzed in the present experiment, including two fertilizer treatments [mineral fertilizer (M) or biogas digestate (D)] applied without biochar (B0), with 3 Mg biochar ha −1 (B3), or with 40 Mg biochar ha −1 (B40). The remaining four treatments ( i.e ., compost with and without 10 Mg biochar ha −1 and fermented biogas digestate with and without 40 biochar ha −1 ) were excluded due to an unbalanced experimental design ( i.e ., they did not feature the biochar levels 0, 3, and 40 Mg ha −1 which were applied with the other six treatments) and they did not receive consistent fertilizer application ( i.e ., all received biogas digestate as fertilizer after 2012).…”
Section: Methodsmentioning
confidence: 99%